Hijab Design and Style in Indonesia which Influenced by Hijabers Community - Puspitasaria, Citra; Dolahrb, Jasni (School of Social Sciences, USM, 2017)
The idea of Indonesia becoming the center of influence in world Muslim fashion in 2020 by Indonesia Islamic Fashion Consortium (IIIF) is strongly feasible, where the industry has been growing significantly since 1990's (Warta Ekspor-Indonesia Ministry of Trade, 2015). This is an interesting phenomenon to be noticed, especially related to hijab (head cover) that has many designs and styles (Rahayu, 2016). Nowadays, hijab has reached a certain prestige as a globalization sign, a symbol of Indonesian Muslim towards other Muslim in another country in a modern world (Ibrahim, 2011). The latest hijab trend in Indonesia appears as a manifestation of paradigm shift of wearing hijab. There is Hijabers Community (HC), a Muslimah community founded in 2010 in Jakarta that accommodates hijab and Muslimah related activities. One of this community's taglines is“From fashion to islamic studies, from hijab style to learning Islam, anything that will make us a better Muslimah insya Allah”. Refered to this tagline, through the design and style of hijab which displayed, HC wants to change the view of the hijab that is synonymous with traditional and ancient, into something modern, fashionable and dynamic (Setiadi, 2013). Some of the initiators of the community are fashion designers who become the influencers towards Indonesian Muslim fashion industry. This research focuses on how hijab design and style changed after HC has been founded in Indonesia and what kind of design aspects which influenced the changes. Further, this is a qualitative research where primary data are gained through field observation and events, as well as interview with respondents HC member and fashion designer. While secondary data gained from related literature review. Finally, result of this research is classification of hijab design and style that is influenced by HC along with its elaboration and conclusion that are related towards the impact of these changes.